Analisis Regresi Multivariate Principle Component Atas Efektifitas E-Tol Dan Kualitas Pelayanan Tol Terhadap Kepuasan Konsumen Jalan Tol Di Serang - Hany Azza Umama; Nurhayani Nurhayani; Anggit Brilianti (Sains: Jurnal Manajemen dan Bisnis, 2019)
This research is an explanatory research that highlights the relationship between research variables and testing hypotheses that have been formulated previoustly by using a sample of 100 people in 4-wheeled vehicle users who often use toll road facilities in the Banten area. Multiple linear regression analysis was used in analyzing the relationship of variables in the study.Based on the results of the analysis, it is known that the effectiveness of the Banten e-toll area, the quality of toll services and the satisfaction of customers of toll road users are considered to be quite good by respondents. The results of partial regression analysis found that the effectiveness of e-toll has significant effect on customer satisfaction at 0.502, while the quality of toll service has a significant effect of 0.528. Simultaneoustly the e-toll effectiveness and service quality have a significant influence.